Determinants of willingness to enroll in opioid agonist treatment among opioid dependent people who inject drugs in Ukraine. (1st August 2016) - Makarenko, Iuliia; Mazhnaya, Alyona; Polonsky, Maxim; Marcus, Ruthanne; Bojko, Martha J.; Filippovych, Sergii; Springer, Sandra; Dvoriak, Sergii; Altice, Frederick L.
Highlights: Interest in receiving OAT was generally low among PWIDs who were not in treatment. Factors associated with interest in OAT differed based on previous OAT experience. Lack of knowledge and negative OAT attitudes are significant obstacles to get OAT. Abstract: Background: Coverage with opioid agonist treatments (OAT) that include methadone and buprenorphine is low (N = 8400, 2.7%) for the 310, 000 people who inject drugs (PWID) in Ukraine. In the context of widespread negative attitudes toward OAT in the region, patient-level interventions targeting the barriers and willingness to initiate OAT are urgently needed. Methods: A sample of 1179 PWID with opioid use disorder not currently on OAT from five regions in Ukraine was assessed using multivariable logistic regression for independent factors related to willingness to initiate OAT, stratified by their past OAT experience. Results: Overall, 421 (36%) PWID were willing to initiate OAT. Significant adjusted odds ratios (aOR) for covariates associated with the willingness to initiate OAT common for both groups included: higher injection frequency (previously on OAT: aOR = 2.7; never on OAT: aOR = 1.8), social and family support (previously on OAT: aOR = 2.0; never on OAT: aOR = 2.0), and positive attitude towards OAT (previously on OAT: aOR = 1.3; never on OAT: aOR = 1.4). Among participants previously on OAT, significant correlates also included: HIV-negative status (aOR = 2.6) and depression (aOR = 2.7). Among participants never on OAT, however, living in Kyiv (aOR = 4.8) or Lviv (aOR = 2.7), previous imprisonment (aOR = 1.5), registration at a Narcology service (aOR = 1.5) and recent overdose (aOR = 2.6) were significantly correlated with willingness to initiate OAT. Conclusions: These findings emphasize the need for developing interventions aimed to eliminate existing negative preconceptions regarding OAT among PWID with opioid use disorder in Ukraine, which should be tailored to meet the needs of specific characteristics of PWID in geographically distinct setting based upon injection frequency, prior incarceration, and psychiatric and HIV status.